Factors associated with malaria in pregnancy among antenatal care mothers at Gulu Regional Referral Hospital in northern Uganda - Oguta, Solomon; Serumaga, Brian; Odongo, Lameck; Otika, Donald; Ayikoru, Jackline; Otim, Raymond; Opee, Jimmyy; Arwinyo, Baifa; Pebalo, Francis Pebolo; Achora, Vincentina; Ojara, Sande; Abola, Benard; et al. (Malaria journal, 2024)
Background All pregnant mothers in Uganda are given sulfadoxine-pyrimethamine (SP, Fansidar ® ) for presumptive treatment of malaria in pregnancy from 14 weeks of gestation, every four weeks, until delivery. However, prenatal mothers still fall sick of malaria. This study aimed to assess the factors associated with malaria in pregnancy among antenatal care mothers at Gulu Regional Referral Hospital. Methods This was a cross-sectional study at Gulu Regional Referral Hospital antenatal clinic from July to August 2023. Consecutive sampling was used. An interviewer-administered questionnaire was used to collect sociodemographic characteristics, physical examination findings and blood samples taken for rapid diagnostic test (RDT) for malaria. A positive RDT was taken as the presence of malaria infection in pregnancy. Data was pre-processed in STATA ® 15, and logistic regression analysis was done in RStudio 4.2.2. Variables with p < 0.05 were taken as independently associated with malaria in pregnancy and reported as adjusted risk ratios (aRR). Results Three hundred fifty (350) pregnant women were recruited; 96% of them slept under mosquito nets daily, while more than half of them (51.7%) had not yet taken SP (IPTp) during their current pregnancy. Prevalence of anaemia (Hb < 11.0 g/dl) was 46.0%. Twenty-four per cent of the mothers were in the first trimester, 56.3% in the second and 19.7% in the third. The prevalence of malaria in pregnancy was 39.7% (95% CI 34.5–45.1%), equally distributed throughout the trimesters. Anaemia (aRR = 4.99, 95%CI 3.10–8.05, p < 0.001) and tertiary level of education (aRR = 0.29, 95% CI 0.14–0.62, p = 0.001) were significantly associated with malaria in pregnancy. Not sleeping under a mosquito net (aRR = 3.79, 95% CI 0.95–15.16, p = 0.059) may be a factor associated with malaria in pregnancy. Conclusion Four in every ten mothers had malaria infection, with anaemia being a risk factor, while a tertiary level of education was protective against malaria in pregnancy.